VD_FINDINFO HC / 2011 / 112 vom 9. Dezember 2010 - VD Tribunal cantonal (2010)
ANNULATION DU MARIAGE, NOUVEAU MOYEN DE PREUVE, LOI FÉDÉRALE SUR LES ÉTRANGERS | 105 ch. 4 CC, 138 al. 1 CC, 374b CPC, 374c CPC, 378 CPC, 444 CPC, 451 ch. 2 CPC, 452 al. 2 CPC